Manejo alternativo de nematoides das lesões radiculares (Pratylenchus zeae e Pratylenchus brachyurus) e reprodução em plantas antagonistas - Santana, Simone de Melo (2014)
Among the alternative methods for the control of nematodes, crop rotation and/or succession with non-host species should be seen as one of the main practices available, since as well as reducing populations of these organisms, implanted crops can also generate financial returns if they are of economic value. They also promote nitrogen fixation, cover crops and mulching when antagonistic leguminous plants are used. Some species have been proven to be efficient in controlling populations of these parasites, although there are relatively few studies available that look into this area in any depth. Therefore, the objective of this study was to evaluate the effect of crop succession with economically important species (Oriza sativa "Ana 9001", "Iapar 9" and "Ecco CL" hybrid, Pennisetum americanun "AMN-17", Gossypium hirsutum cv. IPR 140, Helianthus annuus "Syn 045", Zea mays cv. BRAS 3010, Glycine max cv. BRS 284 and Saccharum spp. cv. RB 72454) on populations of P. zeae and P. brachyurus, and to evaluate the effect of crop succession and intercropping with cover crops (Crotalaria juncea, C. spectabilis, Cajanus cajan cv. Iapar 43, Mucuna deeringiana, Stizolobium aterrimum and Canavalia ensiformis) on lesion nematode populations and identify their penetration capacity. In the experiment involving crop succession with soybean, the results confirmed the difficulty in managing P. brachyurus in this crop, especially when crops that are of high economic value are used. The vegetable species studied were susceptible to the nematode, however rice cv. Iapar 9 presented one of the lowest populations. In the experiment involving crop succession with sugarcane, none of the crops of high economic value presented reductions in nematode populations, as they all presented RF values similar to those obtained for sugarcane and maize. The cover crops studied did not control P. brachyurus when intercropped with soybean, although they all reduced nematode populations in the monocropped systems, with the exception of jack bean. Conversely, the cover crops controlled P. zeae when intercropped with maize, although they all promoted multiplication of the nematode with RF > 1. In the evaluation of RF, Crotalaria spectabilis, C. juncea, dwarf pigeon pea and black velvet bean were resistant to P. zeae. For P. brachyurus, the lowest RF values were provided by C. spectabilis and pigeon pea, while for the other plants, RF values were close to or higher than one in at least one of the experiments.